2012
DOI: 10.1007/s00394-012-0357-x
|View full text |Cite
|
Sign up to set email alerts
|

LDL-cholesterol-lowering effect of a dietary supplement with plant extracts in subjects with moderate hypercholesterolemia

Abstract: Daily consumption of this new DS decreased LDL-cholesterol and TC and is therefore an interesting, convenient aid in managing mild to moderate hypercholesterolemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 48 publications
1
36
0
5
Order By: Relevance
“…At a dosage of 3 tablets/d, the Natural Cholesterol-lowering Supplement provides 500 mg RYR with 2 mg monacolins, 11.1 mg SCdP and 600 mg ALEs with 36 mg caffeilquinic acid, together with minor constituents. Two small-sized randomized controlled trial showed a reduction of LDL-cholesterol concentrations (Ogier;Barrat, 2012). The primary aim of the present study was to confirm such an effect on a larger number of subjects, together with measurements of other parameters relevant to cardiovascular risk and safety assessments.…”
Section: Introductionmentioning
confidence: 90%
“…At a dosage of 3 tablets/d, the Natural Cholesterol-lowering Supplement provides 500 mg RYR with 2 mg monacolins, 11.1 mg SCdP and 600 mg ALEs with 36 mg caffeilquinic acid, together with minor constituents. Two small-sized randomized controlled trial showed a reduction of LDL-cholesterol concentrations (Ogier;Barrat, 2012). The primary aim of the present study was to confirm such an effect on a larger number of subjects, together with measurements of other parameters relevant to cardiovascular risk and safety assessments.…”
Section: Introductionmentioning
confidence: 90%
“…In another study, Ogier et al utilized a daily formulation with only 2 mg of monacolin K in a double-blinded, placebocontrolled trial. 47 Thirty-nine subjects with moderate hypercholesterolemia were randomized to either the red yeast rice formulation or to placebo over the course 16 weeks. At the conclusion of the study, there was a significant reduction in LDL by 19.1% from baseline (P < 0.001) in the subjects in the treatment arm of the study.…”
Section: Red Yeast Ricementioning
confidence: 99%
“…The Panel notes that the three human intervention studies, which were conducted by two independent research groups, showed an effect of the combination of 600 mg artichoke leaf dry extract with 30-36 mg caffeoylquinic acids, 500 mg red yeast rice with 2 mg monacolin K, 10 mg sugar-cane derived policosanols, 20 mg French maritime pine bark extract with 18 mg OPC, 30 mg garlic dry extract with 0.25 mg allicin, 30 mg α-tocopherol equivalents, 5 mg riboflavin and 9 mg inositol hexanicotinate in Limicol ® on LDL-cholesterol concentrations when consumed daily in three doses with the major meals Barrat et al, 2013;Ogier et al, 2013). The Panel also notes that doubling the dose of the food that is the subject of the health claim did not have an additional effect on LDL-cholesterol concentrations .…”
Section: All Three Rcts Identified As Pertinent By the Applicant Invementioning
confidence: 99%